Implementasi Metode Double Diamond Dalam Perancangan UI/UX Aplikasi Halopet Marketplace Layanan Hewan Peliharaan - Mahadevi Katarina Sabila; Seftin Fitri Ana Wati; Prasasti Karunia Farista Ananto (LKP Unity Academy, 2025)
The rapid growth of the pet care industry in Indonesia has not been accompanied by integrated service systems, resulting in various issues such as limited information, inefficient booking processes, and poor schedule management. This study aims to design the UI/UX of the Halopet application as a pet care service platform using the Double Diamond method to produce user-oriented design solutions. The evaluation was conducted using Heuristic Evaluation and Usability Testing based on the ISO 9241-11 standard. The results show an effectiveness score of 97% and an efficiency score of 97.19%, with a System Usability Scale (SUS) score of 92, categorized as excellent. These findings indicate that the proposed application design is capable of improving usability, efficiency, and user satisfaction in accessing pet care services. This study also contributes by proposing an integrated pet care service platform design through a UI/UX approach focused on user experience and a high level of usability.